Survival risk prediction model for ESCC based on relief feature selection and CNN. (June 2022) - Wang, Yanfeng; Zhu, Chuanqian; Wang, Yan; Sun, Junwei; Ling, Dan; Wang, Lidong
Abstract: Esophageal squamous cell carcinoma (ESCC) is a common malignant tumor of the digestive system with poor prognosis and high mortality. It is of great significance to predict the prognosis risk of patients with cancer by using medical pathology information. To take full advantage of the clinic pathological information of ESCC patients and improve the accuracy of postoperative survival risk prediction, this paper proposes an ESCC survival risk prediction model based on Relief feature selection and convolutional neural network (CNN). Firstly, statistical analysis methods and relief feature selection algorithm are used to extract the important risk factors related to the survival risk of patients. Then, One-dimensional convolutional neural network (1D-CNN) is used to establish the survival risk prediction model of patients with esophageal cancer. Finally, the data of patients with esophageal cancer provided by the First Affiliated Hospital of Zhengzhou University is used to assess the performance of the model. The results show that the model proposed in this paper has a high accuracy rate, which can effectively predict the postoperative survival risk of the patient through the clinical phenotypic index of the patient. Graphical abstract: Image 1 Highlights: The relationship between medical indicators and prognosis of esophageal cancer was explored. Screening medical indicators related to the prognosis of esophageal cancer. CNN is used to construct prognostic prediction model of esophageal cancer. The prediction model can accurately predict the prognostic survival risk of patients with esophageal cancer.